2011
DOI: 10.1093/nar/gkr1084
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the RNA binding surface of the pentatricopeptide repeat protein

Abstract: The expressions of chloroplast and mitochondria genes are tightly controlled by numerous nuclear-encoded proteins, mainly at the post-transcriptional level. Recent analyses have identified a large, plant-specific family of pentatricopeptide repeat (PPR) motif-containing proteins that are exclusively involved in RNA metabolism of organelle genes via sequence-specific RNA binding. A tandem array of PPR motifs within the protein is believed to facilitate the RNA interaction, although little is known of the mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
59
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 42 publications
1
59
1
1
Order By: Relevance
“…Perhaps the C-terminal PPR repeats are involved in interaction with RNA cis-elements, whereas the N-terminal repeats mediate interaction with RIP1. Supporting this model is the recent finding that two PPR motifs are sufficient to bind to an RNA target in vitro (55).…”
Section: Discussionmentioning
confidence: 86%
“…Perhaps the C-terminal PPR repeats are involved in interaction with RNA cis-elements, whereas the N-terminal repeats mediate interaction with RIP1. Supporting this model is the recent finding that two PPR motifs are sufficient to bind to an RNA target in vitro (55).…”
Section: Discussionmentioning
confidence: 86%
“…Proteins with arrays of PPRs that are all approximately 35 amino acids long are designated as "P class" proteins. The second type of PPR proteins are designated as "PLS class," 54 residue 34 is also defined as ii according to Kobayashi et al, 54 while the numbering scheme used by Fujii et al 53 is shifted to the N terminus by two amino acids such that amino acids 1, 4 and 34 in the Pfam model are annotated as 3, 6, and 1, respectively. (B) Schematic structures of a typical P class PPr protein, human PTCD3, 84 and a typical PLS class PPr protein, Arabidopsis Crr22.…”
Section: The Modes Of Rna-recognition By Ppr Proteinsmentioning
confidence: 99%
“…53 A detailed study by Kobayashi et al used truncations of the Arabidopsis HCF152 protein, consisting of two adjacent PPRs, to perform extensive mutagenesis to identify amino acids that are important for the affinity or specificity of RNA-binding by these proteins. 54 This study identified residues 1, 4, 8, 12, and 34 as the most important for maintaining high-affinity RNA-binding. The close overlap between the positions identified by co-variation analysis 53 and mutagenesis 54 suggested that these residues play a key role in the recognition of RNA.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…91 Based on the accumulated information on trans-factors (PLS members) and their corresponding RNA editing sites, a statistical study was performed to elucidate the principal components of the PPR code; the study was also based on the research that had focused on the amino acid residues involved in RNA recognition in PPRs. 70,92 In summary, a strong correlation was observed between the combination of positions 6 and 1 on the following PPR (position 1') and the corresponding RNA base (Fig.…”
mentioning
confidence: 99%